Deep Vein Thrombosis in Orthopedic Surgery of the Lower Extremities - Motohashi, Masatoshi (The Editorial Committee of Annals of Vascular Diseases, 2012)
To prevent pulmonary embolism due to deep venous thrombosis (DVT), we have treated 611 patients undergoing orthopedic surgery of the lower extremities with our protocol including pre- and postoperative ultrasonic venous screening and anticoagulant therapy if necessary. A total of 118 patients (19.3%) developed DVT. Among demographic and clinical factors, the site of operation (knee joint surgery: odds ratio 5.17), age (>60: odds ratio 3.91), and operation time (>120 minutes: odds ratio 4.52) were identified as significant risk factors of development of DVT. One patient received an infusion of urokinase for DVT of femoral vein, but no patients developed serious postoperative bleeding or pulmonary thromboembolisms. (*English Translation of J Jpn Coll Angiol, 2010, 50: 95-100.)